The Influence of Organizational Culture, Job Satisfaction and Organizational Justice through Organizational Commitment on the Intention to Leave Employees At PT. Medan Industrial Area: - Aan Nurhadi (ProBisnis : Jurnal Manajemen, 2023)
The purpose of this study was to determine the effect of work placement, workload and organizational culture on work motivation at PT. Medan Industrial Area. The number of samples In this study amounted lo 79 people using the saturated sample technique. The analysis technique used Is multiple linear regression. The results showed that simultaneously work placement variables, workload and organizational culture have a significant effect on employee work motivation. Job placement has no significant effect on employee work motivation, work load and organizational culture have an effect on employee work motivation